Tasting Thomas Hoccleve: Discernment and the Ethics of Judgment in the Series. - Raby, Michael (Modern Philology, 2016)
The article offers poetry criticism of the poem "Series" by Thomas Hoccleve. It explores the judgment ethics and discernment of the poem in the poem. The author discusses the sense of taste test of the poet in association with literary and ethical judgment that is demonstrated through his mirror scene.